The Effect of Axillary Lymph Node Sampling during Mastectomy on Immediate Alloplastic Breast Reconstruction Complications. Issue 5 (May 2019) - Verma, Richa; Klein, Gabriel; Dagum, Alexander; Khan, Sami; Bui, Duc T.
Abstract : Background: Tissue expander-based immediate breast reconstruction is currently the most common technique used for postmastectomy breast reconstruction. During mastectomy, axillary lymph nodes are biopsied to stage patients. The purpose of this study is to investigate postoperative complications with respect to extent of lymph node dissection. Methods: A retrospective review of all patients undergoing tissue expander-based immediate breast reconstruction at our institution from 2010 to 2012 was conducted. Charts were analyzed to determine the association between the absolute number of axillary lymph nodes removed and postreconstructive incidence of skin necrosis, cellulitis, seroma, and expander removal. Independent sample t test and linear regression were used to analyze data. Results: In total, 282 patients with 467 reconstructions were included. Overall incidence of all postoperative complications per breast was 23.8%. Breasts in which a complication occurred had a mean of 6 nodes removed versus 4 nodes in uncomplicated breasts ( P = 0.018). Complications were noted at a significantly higher rate in patients who underwent axillary lymph node dissection compared with sentinel lymph node biopsy ( P = 0.008). Expander removal and seroma occurred more frequently in breasts that had a greater number of nodes removed ( P = 0.006 and P = 0.015, respectively). Preoperative radiation resulted in higher incidence of cellulitis and skin necrosis. Postoperative radiation and chemotherapy did not adversely affect reconstruction. Conclusions: Axillary lymph node removal of >4 nodes confers a greater risk of postreconstructive seroma formation and tissue expander loss in patients undergoing immediate reconstruction following mastectomy. Axillary lymph node dissection has a higher incidence of breast reconstruction complications compared with sentinel lymph node biopsy. Therefore, we encourage plastic surgeons to consider degree of lymphadenectomy when discussing reconstructive options with patients, as this may significantly impact their reconstructive outcome.